Factors That Influence MSME Taxpayers' Willingness to Pay Tax After the Implementation of the Government Rules Number 23 of 2018 - Ratih Kumala (Ilomata International Journal of Tax and Accounting, 2019)
Tax extensification and intensification are one of the government's way of improving tax revenue. Therefore, revenue officers are required to be active, as well as the taxpayers' awareness and willingness. The deficiency of willingness to pay taxes is inseparable from the lack of knowledge, understanding, service, and financial condition of taxpayers and is one of the factors that hinder taxpayer awareness in carrying out their tax obligations. This study aims to analyze the effect of tax awareness, knowledge and understanding of taxation rules, service quality, and financial conditions on the taxpayer readiness of individual income taxpayers. The population used in this study are the taxpayers of BOLU Online Business Community SMEs. The sample used was 100 respondents. The result of this study indicates that the awareness of paying taxes and the quality of service do not significantly influence the willingness to pay taxes. In contrast, knowledge and understanding of tax regulations and financial conditions have a positive influence on taxpayers' willingness to pay.